2022
DOI: 10.1590/fst.01021
|View full text |Cite
|
Sign up to set email alerts
|

Purple wheat alleviates dyslipidaemia in rat model

Abstract: led the implementation of the majority project, conducted majority of the data collection and analysis, and drafting the manuscript. Yaning Meng and Suque Lan contributed to the study equally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Additionally, transcriptome analysis of adipose and liver tissues showed an activation of numerous pathways and genes related to fatty acid-oxidation, anti-oxidative enzymes, as well as balancing fatty acid metabolism, specifically in the black-wheat-supplemented mice group. In a different study, consuming a purple wheat diet for six weeks has been found to reduce lipid metabolism disorder and liver tissue as well as renal injury in hyperlipidemic rats [ 82 ]. A total of 42 rats were randomly divided into four groups, with the normal control group receiving a standard diet, and the other three groups being fed a high-fat diet to induce dyslipidemia.…”
Section: Health-enhancing Properties Of Purple Wheat Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, transcriptome analysis of adipose and liver tissues showed an activation of numerous pathways and genes related to fatty acid-oxidation, anti-oxidative enzymes, as well as balancing fatty acid metabolism, specifically in the black-wheat-supplemented mice group. In a different study, consuming a purple wheat diet for six weeks has been found to reduce lipid metabolism disorder and liver tissue as well as renal injury in hyperlipidemic rats [ 82 ]. A total of 42 rats were randomly divided into four groups, with the normal control group receiving a standard diet, and the other three groups being fed a high-fat diet to induce dyslipidemia.…”
Section: Health-enhancing Properties Of Purple Wheat Foodsmentioning
confidence: 99%
“…The triglyceride, total cholesterol, and low-density lipoprotein levels dramatically decreased to nearly normal levels in the two groups given purple wheat diets. Additionally, the purple wheat diet reduced degeneration of the fatty liver tissue along with mitigation of lipid metabolism disorder and renal injury, which might reverse kidney damage and hepatocyte steatosis caused by dyslipidemia [ 82 ]. On the contrary, feeding broiler rabbits ( n = 18) a pelleted feed mixture containing 15% purple wheat for 61 days showed no significant impact ( p > 0.05) on plasma biomarkers, enzyme activity, hepatic metabolism, total bilirubin concentration, triglycerides, cholesterol, urea, globulin and albumin contents, and antioxidant activities in comparison with the control regular wheat group [ 83 ].…”
Section: Health-enhancing Properties Of Purple Wheat Foodsmentioning
confidence: 99%